THE GROUNDS OF INHERITANCE IN RUSSIAN INHERITANCE LAW - I. Melnikova; M. Komarevtseva (Гуманитарные и юридические исследования, 2021)
The relevance of the research topic is predetermined by enormous practical potential of property inheritance issues. After all, there is no doubt that the law of succession to a certain extent affects the interests of every citizen. The current hereditary legislation is signiicantly different from the Soviet counterpart. Part three of the Civil Code of the Russian Federation, which is the main source of modern inheritance law, demonstrates a qualitatively new level of legal regulation of inheritance relations. At the same time, the Russian hereditary legislation is not without flaws, gaps and contradictions, which applies to the topic of our research. This prompted the authors to turn to the analysis of issues related to the grounds for inheritance. The novelty of this work lies in the attempt to introduce into scientiic circulation new legal constructions stipulated by the Federal Law of 19.07.2018 N217-FZ "On Amendments to Article 256 of Part One and Part Three of the Civil Code of the Russian Federation". This is a hereditary contract as a new basis for inheritance. The study is based on special legal methods: historical and comparative legal. The use of the historical method of research allowed the authors to identify the continuity of the legal regulation of the grounds for inheritance, as well as to evaluate the new legal construction of the "hereditary contract" from the point of view of the traditions of the legal regulation of inheritance relations. The grounds for inheritance are investigated by the authors using a comparative legal approach, which makes it possible to compare Russian and foreign experience in legal regulation in this area in order to identify common principles and differences. The article provides proposals to improve the legal regulation of relations of inheritance based on a hereditary contract.